SMART MONITORING AND SPEAKING MEDICATION REMINDER. - S. V., ASWIN KUMER; KANAKARAJA, P.; NADIPALLI, L. S. P. SAIRAM; A., PUNYA TEJA; T., HARINI SREE; T., TEJASWNI (Turkish Journal of Physiotherapy Rehabilitation, 2021)
The proposed project in this paper is going to deal around monitoring the patient and speaking medication reminder for the medications proposed by the doctor. In health-care surveys medication mix-ups had created a lot more problems. Medication for some chronic diseases which are generally progressive have different types of medicines which are prepared different chemicals and these chronic diseases medicines must be taken in different dosages at particular timings of a day. If these are taken in any kind of improper doses or at wrong timings in a day there will be verse effects with medical mix-ups. People in this rushed daily routine generally forgets to take medication in proper timing and in proper dosages. So we are proposing a project that reminds patients at particular timings to take preferred dosages referred by doctors. The device itself speaks out the dosages that are taken by the patient which are already provide as input through keyboard. The device itself converts the input text into voice commands and speaks out loud so that the patient can hear and take the medication in proper timing and in proper amount. And this device is also integrated with a web cam which can be accessed through anywhere so we can also track the patient current position and status by viewing him from our device. The whole set up is connected to Wi-Fi and IoT data base so we can store every data in cloud so we can access the data of particular medication of every patient which is useful for surveys and improvements.